Altered age‐linked regulation of plasma DYRK1A in elderly cognitive complainers (INSIGHT‐preAD study) with high brain amyloid load. Issue 1 (2nd July 2020) - Delabar, Jean M.; Ortner, Marion; Simon, Stephanie; Wijkhuisen, Anne; Feraudet‐Tarisse, Cecile; Pegon, Jonathan; Vidal, Emma; Hirschberg, Yael; Dubois, Bruno; Potier, Marie‐Claude
Abstract: Introduction: An effective therapy has not yet been developed for Alzheimer's disease (AD), in part because pathological changes occur years before clinical symptoms manifest. We recently showed that decreased plasma DYRK1A identifies individuals with mild cognitive impairment (MCI) or AD, and that aged mice have higher DYRK1A levels. Methods: We assessed DYRK1A in plasma in young/aged controls and in elderly cognitive complainers with low (L) and high (H) brain amyloid load. Results: DYRK1A level increases with age in humans. However, plasma from elderly individuals reporting cognitive complaints showed that the H group had the same DYRK1A level as young adults, suggesting that the age‐associated DYRK1A increase is blocked in this group. L and H groups had similar levels of clusterin. Discussion: These results are reflective of early changes in the brain. These observations suggest that plasma DYRK1A and not clusterin could be used to classify elderly memory complainers for risk for amyloid beta pathology.